Fragile growth coalitions or powerful contestations? Cancelled Olympic bids in Boston and Hamburg. (August 2017) - Lauermann, John; Vogelpohl, Anne
Hosting sports "mega-events" like the Olympics is a common scenario among urban growth coalitions worldwide. They are promoted as temporary "catalysts" for local economic growth linked to exceptional decisions in land provision and public spending. But this model of growth politics is increasingly contested: recent Olympic bids have failed in a number of cities as urban social movements organize against them while growth coalitions are unable or unwilling to defend their projects. Two cities exemplify this changing political economic landscape: Boston (USA) and Hamburg (Germany). Both cities launched bids for the 2024 Summer Olympics, and both cities subsequently cancelled their bids. Drawing on a comparative study of bidding politics in Boston and Hamburg, the paper asks why growth policy failed, analyzing the conflict between opposition movements and long-established growth coalitions. These episodes are symptoms of a growth coalition fragility that weakens their effectiveness in urban politics. Urban growth coalitions must contend with changing growth priorities and leadership; by triggering fragility, protest movements are able to gain new influence on the urban policy agenda.